The existence of Gorenstein flat covers - Enochs, Edgar E.; Jenda, Overtoun M. G.; Lopez-Ramos, J. A. (MATHEMATICA SCANDINAVICA, 2004)
We prove that all left modules over a right coherent ring have Gorenstein flat covers.